Factors influencing the usage, restrictions, accessibility, and preference of urban neighborhood parks - A review of the empirical evidence - Zhao, Jing; Aziz, Faziawati Abdul; Ujang, Norsidah (Elsevier GmbH, 2024)
Urban neighborhood parks hold significance in the lives of all inhabitants of a city. Numerous research studies suggest that neighborhood parks serve a crucial function in affording urban residents the chance to engage with nature, participate in physical exercise, as well as establish social connections. Accessibility to neighborhood parks and other natural spaces benefits residents' physical and mental health. The majority of research has found that either active or inactive involvement with natural surroundings reduces the incidence of emotions such as sadness, stress, and anxiousness. Notwithstanding certain indications that urban neighborhood parks are underutilized due to concerns about their quality, safety, and proximity, a comprehensive evaluation of these parks is yet to be conducted. Consequently, there exists a significant interest in comprehending how community residents engage with and utilize local parks. This research conducts a comprehensive analysis of the pertinent literature from various disciplines, including sociology, economics, geography, and ecology, among others. It employs a systematic review methodology to gather diverse characteristics of urban neighborhood parks, such as utilization, accessibility, contentment, and inclination. This study comprises a total of 20 (N = 20) articles about urban neighborhood parks, which were obtained through a thorough review of the literature throughout seven search engines, including the scientific databases Science Direct, Google Scholar, the World Wide Web of Science, the ProQuest, Scopus, and the CNKI, among others Dissertation & Theses. The articles were selected based on their connection with the topics of urban neighborhood parks, public urban green spaces, park usage, preferences, mental health, and other related keywords. This literature review provides an analysis of the sample features, collecting data methods, sampling strategies, analysis of data, as well as significant results. The selected research has consistently documented the significance of urban neighborhood parks in promoting mental well-being, followed by social advantages. However, only a few studies have investigated the possible benefits of urban neighborhood parks in facilitating physical activities. The correlation between human health and the perceived inclination towards a verdant environment, as well as the emotional connection to factors such as tranquility, security, and physical well-being, has been extensively documented.